Correlation between Transient Response and Neuromorphic Behavior in Organic Electrochemical Transistors (Adv. Electron. Mater. 4/2022). (10th April 2022) - Yamamoto, Shunsuke; Polyravas, Anastasios G.; Han, Sanggil; Malliaras, George G.
Abstract : Organic Neuromorphic Devices The working mechanism of neuromorphic devices on organic electrochemical transistors is investigated in article 2101186 by Shunsuke Yamamoto and co‐workers. The experimental and modeling results highlight the importance of the ionic movements in the device. These insights pave the way for a rational design of OECT‐based neuromorphic devices.